2009
DOI: 10.1093/geront/gnp051
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Job Satisfaction, Overall Satisfaction, and Intention to Leave the Job Among Nursing Assistants in Nursing Homes

Abstract: Intrinsic satisfaction and extrinsic job factors amenable to change appear central to NAs' overall satisfaction and intention to leave. A facility may be able to improve extrinsic job factors that improve NAs' job-related affects, including intrinsic satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
87
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 30 publications
12
87
1
Order By: Relevance
“…Such findings are consistent with other studies that found that DCWs who had positive views of their supervisors were less likely to leave (Brannon et al, 2007; Ng & Sorensen, 2008). Though other research has demonstrated the inverse effects of supervisory support on intention to quit through the mediating variable of job satisfaction (Decker, Harris-Kojetin, & Bercovitz, 2009; Dupré & Day, 2007), we found a direct association between supervisory support and low intentions to quit.…”
Section: Discussioncontrasting
confidence: 99%
“…Such findings are consistent with other studies that found that DCWs who had positive views of their supervisors were less likely to leave (Brannon et al, 2007; Ng & Sorensen, 2008). Though other research has demonstrated the inverse effects of supervisory support on intention to quit through the mediating variable of job satisfaction (Decker, Harris-Kojetin, & Bercovitz, 2009; Dupré & Day, 2007), we found a direct association between supervisory support and low intentions to quit.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous research has found that the quality of the supervisory relationship, as assessed by the direct care worker, can be an important predictor of overall job satisfaction and retention (Bishop, et al, 2008; Chou, 2012; Decker, Harris-Kojetin, & Bercovitz, 2009). Additionally, feeling supported by the agency and facility where they work, has also been found to influence direct care worker job satisfaction and, when positive, to lower turnover (Bowers, Esmond, & Jacobson, 2003; Eaton, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that having enough time to assist nursing home residents with daily activities and being respected were two variables responsible for job satisfaction. 11,12 The conflict between feeling certain and having too much responsibility and being accompanied by uncertainty and too little formal power in trying to do what is right and good was one of the findings in Hov et al's 13 study of nurses working in nursing homes. These authors also noted that caring for patients in a nursing home meant being a vulnerable helper, feeling undervalued and needing emotional protection.…”
Section: Introductionmentioning
confidence: 99%